ALFRED SCHÜTZ AND THE OPEN HORIZONS OF PHENOMENOLOGICAL SOCIOLOGY: THE CONSTITUTION OF THE INTERSUBJECTIVE STRUCTURE, AND THE THOU-ORIENTATION - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2012)
The aim of this essay is to articulate and explicate the relations between sociological theory and the phenomenological approach. This is done in two parts: the first looks at Schutz’s attempts to articulate a constitutive phenomenology of the natural attitude; the second explicates the methodological postulates formulated by Schutz for the construction of social scientific constructs. It is suggested that the nature of the conventional sociological inquiry in Lithuania must be reconsidered if the subjective view of actor is to be retained as relevant to both philosophical and sociological inquiry. Key words: a constitutive phenomenology of the natural attitude, Alfred Schutz, social theory, phenomenology in Lithuania, the three relevant horizons of social action: philosophy, sociology and culture.